INTERVENSI PENYEBAB COUNTERPRODUCTIVE WORK BEHAVIOR PADA PENGASUH PANTI ASUHAN XYZ - Riyadi, Astri; Gracious, Levi; Dewanto, Hajar; Savitry S Pandia, Weny; Maysha, Linda (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
XYZ Foundation is an orphanage specifically for children with special needs who need more intensive services thantypical children. From the initial meeting with XYZ Orphanage, complaints were made about CounterproductiveWork Behavior (CWB) problems in caregivers. CWB itself is defined as a form of dysfunctional behavior anddetrimental to both individuals and organizations. CWB that appears to caregivers is that some caregivers seemnegligent in doing tasks and lack enthusiasm in working. Caregivers also seem to lack information related to therules that have been set so that caregivers often violate the rules. In addition, some caregivers are also found tooften talk about superiors and there are feelings of mutual dislike which are often caused by misunderstandingsbetween caregivers. In the end, the atmosphere in the caregiver group environment seemed negative so that thecaregivers did not help each other, and the caregiver's work was heavy. Poor caregiver performance causes childrennot to get maximum care and can have an impact on child development. The emergence of counterproductivebehavior in XYZ Orphanage is caused by problems in task preparation, job related information, organizationalinjustice, and less positive group dynamics that have an impact on the emergence of counterproductive workbehavior (CWB) in the caregiver group. Thus, interventions are made on these aspects so that XYZ Orphanagecaregivers can work more optimally. Interventions made are training and team building to cope with problems intask preparation and group dynamics, also compiled a standard operational procedure of caregiver to solve problemin job related information. Some suggestions also given to help the orphanage manage key performance indicatorsto cope with organizational injustice. ABSTRAK: Yayasan XYZ merupakan panti asuhan yang dikhususkan untuk anak berkebutuhan khusus yang membutuhkanpelayanan yang lebih intensif dibandingkan anak tipikal. Dari pertemuan awal dengan pihak Panti XYZ, dikeluhkanadanya permasalahan Counterproductive Work Behavior (CWB) yang ada pada pengasuh. CWB sendirididefinisikan sebagai bentuk perilaku disfungsional dan merugikan baik bagi individu maupun organisasi. CWByang tampak pada pengasuh adalah beberapa pengasuh tampak lalai dalam mengerjakan tugas dan kurangbersemangat dalam bekerja. Pengasuh juga tampak kurang mengetahui informasi terkait peraturan yang sudahditetapkan sehingga pengasuh seringkali melanggar peraturan. Selain itu beberapa pengasuh juga didapati seringmembicarakan atasan dan adanya perasaan saling tidak suka yang seringkali disebabkan oleh kesalahpahaman antarpengasuh. Pada akhirnya, suasana di lingkungan kelompok pengasuh tampak negatif sehingga pengasuh tidak salingmembantu dan pekerjaan pengasuh terasa berat. Performa pengasuh yang kurang baik menyebabkan anak-anak tidakmendapatkan pengasuhan yang maksimal dan dapat berdampak pada perkembangan anak. Timbulnyacounterproductive behavior di Panti Asuhan XYZ diakibatkan oleh permasalahan pada task preparation, job relatedinformation, adanya organizational injustice, dan dinamika kelompok yang kurang positif sehingga berdampak padatimbulnya perilaku counterproductive work behavior (CWB) pada kelompok pengasuh. Dengan demikian,dilakukan intervensi pada aspek-aspek tersebut agar pengasuh panti asuhan XYZ dapat bekerja lebih optimal.Intervensi yang dilakukan adalah pelatihan dan team building untuk mengatasi masalah dalam task preparation dandinamika kelompok. Peneliti juga menyusun prosedur operasional standar pengasuh untuk memecahkan masalahdalam job related information. Beberapa saran juga diberikan untuk membantu panti asuhan mengelola indikatorkinerja utama untuk mengatasi organizational injustice.